2020
DOI: 10.4269/ajtmh.20-0623
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Outcomes, and Risk Factors for Mortality in Critically Ill Women Admitted to an Obstetric High-Dependency Unit in Sierra Leone

Abstract: A better understanding of the context-specific epidemiology, outcomes, and risk factors for death of critically ill parturients in resource-poor hospitals is needed to tackle the still alarming in-hospital maternal mortality in African countries. From October 2017 to October 2018, we performed a 1-year retrospective cohort study in a referral maternity hospital in Freetown, Sierra Leone. The primary endpoint was the association between risk factors and highdependency unit (HDU) mortality. Five hundred twenty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Intensive intermediate Obstetric Critical Care is needed to address maternal complications and their sustainability low resource setting. Studies conducted in Sierra Leone showed an additional cost per QALY of only 10.0; the implementation and one-year running of the case studied obstetric a highly cost-effective innovation [17]. Cost-effective, proven Obstetric Critical Care is needed to address maternal complications.…”
Section: Plos Onementioning
confidence: 99%
“…Intensive intermediate Obstetric Critical Care is needed to address maternal complications and their sustainability low resource setting. Studies conducted in Sierra Leone showed an additional cost per QALY of only 10.0; the implementation and one-year running of the case studied obstetric a highly cost-effective innovation [17]. Cost-effective, proven Obstetric Critical Care is needed to address maternal complications.…”
Section: Plos Onementioning
confidence: 99%
“…The major causes of maternal deaths in Africa are infections, postpartum hemorrhage, high blood pressure (preeclampsia and eclampsia), complications from delivery and unsafe abortion. [2][3][4][5] Substantial expenditure due to maternal complications could create a heavy economic burden to the households. Even when medical services are offered at reasonable prices or free of charge, indirect medical expenses associated with treatment may constitute a larger proportion of household income.…”
Section: Introductionmentioning
confidence: 99%
“… 32 This does not imply a causal relationship with mortality, as parturients largely die of direct obstetric complications such as hemorrhage, eclampsia, and sepsis. 3 , 33 Yet, pulmonary complications led to frequent escalation of care. Although most obstetric critical illness can be treated in medium care units, 3 , 34 intensive care unit beds and mechanical ventilators are scarcely available in Africa.…”
Section: Discussionmentioning
confidence: 99%